Spectrum of rare and common genetic variants in arrhythmogenic cardiomyopathy. (3rd October 2022) - Lippi, M; Chiesa, M; Ascione, C; Pedrazzini, M; Mushtaq, S; Rovina, D; Riggio, D; Di Blasio, A; Biondi, M L; Pompilio, G; Colombo, G I; Novelli, V; et al.
Abstract: Background: Arrhythmogenic cardiomyopathy (ACM) is a rare inherited cardiac disorder, whose genetic cause is elusive in about 50% of cases. ACM pathogenic mutations mainly involve desmosomal genes (PKP2, JUP, DSP, DSG2, DSC2). ACM presents a variable disease course, spanning from mild electrocardiographic alterations and/or contractile dysfunctions, to malignant ventricular arrhythmias and heart failure. Purpose: In an attempt to broaden etiological diagnosis for ACM patients, this work was aimed at finding potential rare high-impact variants in genes not previously associated with ACM. Secondarily, we meant to assess the impact of genetic polymorphisms on the disease clinical severity. Methods: We clinically characterized 82 consecutive ACM probands and performed next-generation sequencing, exploring a panel of 174 genes associated with inherited cardiovascular diseases. We evaluated the pathogenicity of rare variants, according to the American College of Medical Genetics / Association for Molecular Pathology guidelines, to select candidates with potential ACM causative role. Further, a genotype-phenotype correlation analysis between common polymorphisms and clinical variables was performed to find genetic factors associated with specific ACM phenotypes. Finally, we carried out event-free survival analyses, linking specific variants to arrhythmias in 8, 6±0, 7 years follow-up, to estimate their possible impact on arrhythmic risk. Results: We identified 141 rare genetic variants, of which 23 were classified of high impact, including variants in genes never associated with ACM (e.g. ABCC9, APOB, MIB1). These genes deserve future studies as they could participate in ACM pathogenesis. In addition, we found 69 genotype-phenotype significant associations (p≤0.005) between common variants and clinical parameters. Variants associated to arrhythmic phenotypes were found with genes linked to arrhythmias (e.g. KCNQ1, HCN4) and other cardiomyopathies (e.g. MYBPC3, MYL2). Associations involving substrate impairments were found with genes linked to muscle dysfunctions (e.g. LAMA2, SGCD). Arrhythmia-associated polymorphisms, included in survival analyses, were found to be associated with an increased occurrence of arrhythmic events during patients' follow-up. Conclusion: The identification of rare high impact variants in novel genes potentially associated with ACM and the observation of genotype-phenotype correlations constitute the starting point to address the current lack of knowledge of the genetic landscape of ACM. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero Italiano della Salute - Ricerca corrente